Preparation and use methods of modified cerium oxide nano-abrasive
Through the modification treatment of silane coupling agent and short-chain organic acid, the problem of poor suspension stability of cerium oxide abrasives under alkaline conditions is solved, and more efficient polishing effect and more stable suspension performance are achieved.
Patent Information
- Application Number
- CN202411469443.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, cerium oxide abrasives are prone to agglomeration under alkaline polishing conditions, resulting in poor suspension stability, low polishing efficiency, poor suspension performance, and difficult to clean.
The modification treatment is carried out by using silane coupling agent and short-chain organic acid. The electrostatic repulsion and steric hindrance of cerium oxide nanoparticles are increased through chemical reactions, forming amide bonds, and improving their suspension stability and dispersion ability.
The suspension stability and dispersion of cerium oxide nanoabsorbates are improved, so that they remain stable in the aqueous suspension for more than 2 months, and the polishing efficiency and suspension performance are improved.
Smart Images

Figure CN119307231A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth materials, and in particular to a preparation and use method of a modified cerium oxide nano-abrasive. Background Art
[0002] With the rapid advancement of the semiconductor technology industry, higher requirements are placed on the performance of CMP polishing liquid, especially in highly integrated chips. The development of safer, more stable, more efficient and more environmentally friendly CMP polishing liquid is on the agenda. Compared with other solvents, water-based polishing liquid with water as solvent reduces the use and emission of volatile organic compounds, has little pollution to the workpiece, is easy to clean, and is considered to be an environmentally friendly polishing liquid that is widely used now because of its low toxicity, human body and environmental friendliness and many other advantages. However, due to the low viscosity of water-based polishing liquid and the fact that the abrasive size usually reaches the micron level, it is very easy to agglomerate. Improving the dispersibility and stable suspension in water-based polishing liquid is the key issue.
[0003] Compared with other abrasives. Cerium oxide, known as the "king of polishing powder", is amphoteric under alkaline polishing conditions and can adsorb both anions and cations at the same time. It is superior to other products in polishing efficiency and effect. However, under the current process technology route, the industrially produced CeO2 abrasive particles have irregular morphology and a large particle size distribution range, which makes the suspension stability of the polishing liquid and its polishing quality unstable. When using cerium oxide polishing powder as an abrasive to prepare polishing liquid, cerium oxide is very easy to agglomerate due to its high surface energy, which can easily cause scratches on the workpiece; secondly, it has poor suspension performance and is easy to adhere to the surface of the workpiece. The abrasive sinks to the bottom and clumps, resulting in reduced polishing efficiency, which also brings difficulties to subsequent cleaning.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a method for preparing a modified cerium oxide nano-abrasive. The method has a strong process technology route operability, can be scaled up in batches, and has a high utilization rate. At the same time, the preparation method can make the particle size of the nano-cerium oxide abrasive uniform, and can improve its suspension and dispersion stability when configured into an aqueous suspension without other additives.
[0006] The second object of the present invention is to provide a method for using the modified cerium oxide nanoabrasive, which can effectively improve its suspension performance.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: The present invention provides a method for preparing a modified cerium oxide nanoabrasive, comprising the following steps: Pre-treating cerium carbonate to obtain cerium oxide nanoparticles; The cerium oxide nanoparticles are mixed with a toluene solution containing a silane coupling agent, heated and stirred in an oil bath for reaction, centrifuged, washed with ethanol, and dried to obtain a cerium oxide intermediate; The short-chain organic acid is prepared into an aqueous solution, the cerium oxide intermediate is mixed with the short-chain organic acid aqueous solution, heated in an oil bath and stirred for reaction, centrifuged, washed with ethanol, and dried to obtain; The mass ratio of the cerium oxide nanoparticles to the silane coupling agent = (30:1) - (5:1); The mass ratio of the cerium oxide intermediate to the short-chain organic acid is (30:1)-(5:1).
[0008] In the present invention, the toluene solution containing the silane coupling agent is used as a modifier to modify the cerium oxide nanoparticles through a chemical reaction. It increases the electrostatic repulsion between the particles by firmly combining with the cerium oxide nanoparticles, effectively improving the dispersion ability of the cerium oxide nanoparticles, thereby achieving the effect of improving their suspension stability.
[0009] Since the reaction time of the reaction system of the present invention is long and the reaction temperature is high; when using traditional water bath heating, it is difficult to exceed the reaction temperature of 100°C. In addition, long-term water bath heating is likely to cause evaporation of water, thereby affecting the reaction. Therefore, in the present invention, an oil bath method is selected to perform the reaction, which can reach a higher reaction temperature and is not prone to evaporation during the reaction.
[0010] In the present invention, a short-chain organic acid is selected to modify the cerium oxide intermediate, and the surface of the cerium oxide nanoabrasive obtained after coupling with a silane coupling agent is connected to an amino group to form a cerium oxide intermediate. The short-chain organic acid can be coupled with the cerium oxide intermediate to form an amide bond; the amide bond on its surface can enable the amino acid to be coupled to the periphery of the Si-O-Ce bond to achieve co-modification, thereby modifying the cerium oxide nanoabrasive and further improving its suspension stability.
[0011] Since the silane coupling agent and the short-chain organic acid aqueous solution used in the present invention are both used as modifiers, their dosage needs to be limited. When the proportion of the silane coupling agent is low, the cerium oxide nanoabrasive cannot be fully modified, thereby affecting its performance; and when its content is too high, in addition to causing unnecessary waste, it is also easy to produce other uncontrollable reactions caused by reacting under long-term or high-temperature conditions. When the content of the short-chain organic acid is low, some cerium oxide intermediates are difficult to be modified, which will make the quality of the modified abrasive produced uneven and unstable; when the content of the short-chain organic acid is high, the short-chain organic acid itself may undergo an oxidation-reduction reaction to produce impurities, and the cerium oxide intermediate cannot be fully modified. Therefore, in the present invention, the mass ratio of cerium oxide nanoparticles to silane coupling agent is limited to (30:1)-(5:1); the mass ratio of cerium oxide intermediate to short-chain organic acid is limited to (30:1)-(5:1) to achieve the optimal reaction conditions.
[0012] Preferably, as a further specific implementation, the mass ratio of the cerium oxide nanoparticles to the silane coupling agent is 10:1; Preferably, the mass ratio of the cerium oxide to the short-chain organic acid is 10:1.
[0013] Further exploration under the above-mentioned limited conditions showed that the mass ratio of cerium oxide nanoparticles to silane coupling agent = 10:1, and the mass ratio of cerium oxide to short-chain organic acid = 10:1, which enabled the two modifiers to better modify cerium oxide, making the abrasive more uniform, stable and easier to disperse.
[0014] Preferably, as a further specific embodiment, the silane coupling agent is γ-aminopropyltriethoxysilane (C9H 23 NO3Si, KH550), γ-aminopropyltrimethoxysilane (C6H 17 NO3Si, KH-540), γ-(2,3-epoxypropyl)propyltrimethoxysilane (C9H 20 O5Si, KH560), γ-mercaptopropyltrimethoxysilane (C6H 16 O3SSi, KH590), γ-(methacryloyloxy)propyltrimethoxysilane (C 10 H 22 O4Si, KH570), 3-mercaptopropyltriethoxysilane (C9H 22 O3SSi, KH580), γ-aminoethylaminopropyltrimethoxysilane (C8N2H 20 O3Si, KH792), N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (C8H 22 N2O2Si, KH602), γ-methacryloxypropylmethyldimethoxysilane (C10 H 20 O4Si, KH571) or a mixture of any one or more thereof.
[0015] When selecting a coupling agent, a coupling agent containing silane is preferred because the silane coupling agent can easily form a Si-O-Ce chemical bond with cerium oxide, so that the silane coupling agent can be bridged on the surface of cerium oxide, forming a stable cerium oxide intermediate that is easy to be modified later, which helps to improve the stability of the modified cerium oxide nanoabrasive.
[0016] Preferably, as a further specific embodiment, the silane coupling agent is a mixture of γ-aminopropyltriethoxysilane and / or γ-mercaptopropyltrimethoxysilane, and any one of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-aminopropyltrimethoxysilane or 3-mercaptopropyltriethoxysilane is added.
[0017] In the present invention, the silane coupling agent itself will also undergo hydrolysis during the reaction process with the cerium oxide nanoabrasive, and the hydrolysis process will also be accompanied by the self-condensation of the silane group. The chemical group formed by the self-condensation can form a hydrogen bond with the group on the surface of the cerium oxide intermediate, and dehydration condensation is converted into a covalent bond under heating conditions. Therefore, in this process, different silane coupling agents are selected to make themselves undergo self-condensation, which can better chemically combine with the surface of the cerium oxide abrasive to form Si-O groups, and the formed coating is more stable, and can better and more reasonably provide steric hindrance, thereby improving the dispersibility of the modified cerium oxide nanoabrasive.
[0018] Preferably, as a further specific embodiment, the short-chain organic acid is a mixture of any one or more of glutamic acid, aspartic acid, cysteine, serine, threonine, histidine, glycine, tryptophan, phenylalanine, leucine, methionine, cystine, tyrosine, arginine, isoleucine, proline asparagine, citric acid, and ethylenediaminetetraacetic acid; Preferably, the short-chain organic acid is glutamic acid.
[0019] In the present invention, due to the consideration of steric hindrance, short-chain organic acids are selected to react with the cerium oxide intermediate. Long-chain organic acids not only affect steric hindrance, increase the difficulty of coupling or fail to couple successfully, but even if the coupling is successful, the long-chain groups will also affect each other, resulting in a decrease in the uniformity and dispersibility of the modified cerium oxide nanoabrasive. At the same time, the above-mentioned short-chain organic acids can form a final structure with the cerium oxide intermediate, and the modification is achieved by forming a reasonable steric hindrance, thereby achieving the purpose of improving its suspension effect.
[0020] Preferably, as a further specific embodiment, in the step of mixing the cerium oxide nanoparticles with a toluene solution containing a silane coupling agent, and heating and stirring the mixture in an oil bath, the temperature of the oil bath is 40°C-110°C, and the time of the oil bath is 2h-12h; Preferably, the temperature of the oil bath is 80°C and the time of the oil bath is 5 hours.
[0021] In the present invention, the temperature and time of the oil bath are limited. The temperature of the oil bath affects the bridging of the silane coupling agent of the cerium oxide. If the temperature is too high, it exceeds the boiling point of toluene, resulting in coupling failure; and if the temperature of the oil bath is too low, the silane coupling agent cannot bridge to the surface of the cerium oxide. The reaction time will affect the progress of the reaction. If the reaction time is too short, it is difficult to have an effective reaction. If the reaction time is too long, side reactions may occur, resulting in unnecessary waste.
[0022] Preferably, as a further specific embodiment, in the step of mixing the cerium oxide intermediate with the short-chain organic acid and heating and stirring the reaction in an oil bath, the temperature of the oil bath is 40°C-120°C, and the time of the oil bath is 2h-12h; Preferably, the temperature of the oil bath is 80°C and the time of the oil bath is 5 hours.
[0023] Under the reaction temperature and reaction time, the cerium oxide intermediate combines with the short-chain organic acid with higher efficiency, which is more suitable for the reaction system of the present invention.
[0024] Preferably, as a further specific embodiment, the pre-treatment step includes calcination, the calcination temperature is 400°C-1200°C, and the calcination time is 6h-48h; Preferably, the calcination temperature is 800°C and the calcination time is 30h.
[0025] The pretreatment process includes calcining cerium carbonate, so the calcination temperature and time are limited. The calcination temperature directly affects the generation of cerium oxide precursor. When the calcination temperature is too low or the calcination time is too short, cerium carbonate cannot be decomposed and the cerium oxide precursor cannot be obtained. When the calcination temperature is too high or the calcination time is too long, the generated cerium oxide will agglomerate, causing it to sink to the bottom in subsequent ball milling, affecting the ball milling effect.
[0026] The present invention also provides a method for using the modified cerium oxide nanoabrasive, comprising the following steps: The modified cerium oxide nano-abrasive is mixed with water to form a suspension, and the solid content is maintained at 1%-20%.
[0027] Compared with the prior art, the present invention has the following beneficial effects: The surface of the nano-abrasive prepared by the preparation method is co-modified with the functional groups of a silane coupling agent and an organic carboxylic acid; the process technology route is highly operable, can be scaled up in batches, and has a high utilization rate; the modified cerium oxide nano-abrasive prepared by the preparation method of the invention can maintain its suspension (D50) for up to 2 months without the action of any additives. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 : Infrared spectrum of cerium oxide nanoparticles modified by KH550 under the calcination conditions of 400°C-1200°C in Example 1.
[0029] Figure 2 : Infrared spectra of cerium oxide nanoparticles modified by KH550, KH560 and KH590 in Example 4.
[0030] Figure 3 : IR spectra of cerium oxide nanoparticles modified with KH550, glutamic acid and aspartic acid. DETAILED DESCRIPTION
[0031] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0032] Example 1 2000 g of cerium carbonate was calcined in a muffle furnace at 700 °C for 24 h, and then ground to obtain a cerium oxide precursor. 500 g of the cerium oxide precursor was weighed and placed in a 5 L ball mill, ground for 12 h, and then centrifuged, washed with deionized water and anhydrous ethanol, and dried to obtain cerium oxide nanoparticles.
[0033] The silane coupling agent selected in this embodiment is γ-aminopropyltriethoxysilane (C9H 23 NO3Si, KH550), hereinafter referred to as KH550.
[0034] The above 5 g of cerium oxide nanoparticles, 0.5 g of KH550, and 100 mL of toluene were mixed in a 250 mL round-bottom flask and placed in a stirrer with oil bath heating. When the oil bath temperature reached 80 °C, the timing was started. After 5 h of reaction, the solid obtained by centrifugation was washed with deionized water and anhydrous ethanol, vacuum dried, and ground to obtain a cerium oxide intermediate. The above 5 g of cerium oxide intermediate, 0.5 g of glutamic acid, and 100 mL of deionized water were mixed in a 250 mL round-bottom flask and placed in a stirrer with oil bath heating. When the oil bath temperature reached 80 °C, the timing was started. After 5 h of reaction, the solid obtained by centrifugation was washed with deionized water and anhydrous ethanol, vacuum dried, and ground to obtain the co-modified modified cerium oxide abrasive.
[0035] Take 2 g of the modified cerium oxide abrasive in the embodiment and the comparative example and 198 g of deionized water to prepare a 1% cerium oxide abrasive suspension, take 5 mL of the suspension 25 mL below the liquid surface to measure its initial solid content, and place it in a constant temperature environment at 20 ° C for 1 h, 2 h, 4 h, 8 h, 16 h (subsequently tested every 8 h), and so on, until the measured value is 50% of the initial value, and record the time at this time.
[0036] Example 2 The specific implementation method is consistent with Example 1, only the muffle furnace calcination temperature and time are changed, and cerium oxide nanoparticles are obtained after calcination at 400°C, 800°C, and 1200°C for 6 h, 30 h, and 48 h, respectively. The infrared spectrum of the KH550@CeO2 sample shows Figure 1 It can be seen that the 2360 cm -1 and 980 cm -1 The same characteristic peak as KH550 is found on the CeO2 surface, indicating that KH550 is successfully bridged to the CeO2 surface.
[0037] The cerium oxide nanoabrasive was prepared by referring to the preparation method of Example 1 to prepare a 1% cerium oxide abrasive suspension. The D50 value thereof was measured according to the suspension property measurement experiment in Example 1. The experimental results are shown in Table 1.
[0038] Table 1: Effects of different calcination temperatures and calcination times on the suspension properties of modified cerium oxide nanoabrasives
[0039] It can be seen from the experimental data of Example 2 that different calcination temperatures have an important influence on the suspension stability of the cerium oxide nano-abrasive suspension. Temperature and time affect the particle size. At a suitable temperature, the generated cerium oxide nano-abrasive particles are uniform in size, and thus perform well in the subsequent suspension determination process. High temperature and long time will agglomerate and cause the generation of large particles (harmful particles), resulting in a decrease in its suspension stability, while low temperature and short time are not conducive to the generation of cerium oxide nano-precursors.
[0040] Example 3 The specific implementation method is consistent with Example 1, using different silane coupling agents: When KH550 was used, the KH550@CeO2 sample was obtained; When KH560 was used, the KH560@CeO2 sample was obtained; When KH590 was used, the KH590@CeO2 sample was obtained; When KH602 was used, the KH602@CeO2 sample was obtained; When KH517 was used, the KH517@CeO2 sample was obtained; When KH550 is used, KH560 is added to obtain KH550&KH560@CeO2 sample; When KH550 and KH590 are used, KH560 is added to obtain KH550&KH590&KH560@CeO2 samples; When KH550 is used, KH560 and KH540 are added to obtain KH550&KH560&KH540@CeO2 samples; The D50 value was determined according to the suspension test in Example 1, and the experimental results are shown in Table 2. The infrared spectra of KH550@CeO2, KH560@CeO2 and KH590@CeO2 samples are shown in Figure 2 It can be seen that in the KH560@CeO2 sample at 2940 cm -1 , 1100 cm -1 , 1040 cm -1 At 1060 cm -1 The features are obviously different from those of CeO2, indicating that KH560 and KH590 are successfully bridged on the CeO2 surface.
[0041] Table 2: Effect of different silane coupling agents on the suspension properties of modified cerium oxide nanoabrasives
[0042] It can be seen from the experimental data of Example 3 that the functional groups of different silane coupling agents have an important influence on the suspension stability of the modified cerium oxide nanoabrasive suspension. Generally speaking, the rear functional group is a hydrophilic group (for example, the end of KH550 is an amino group (-NH2)), which is easy to form a chemical bond with an organic carboxylic acid (amino group and carboxylic acid form an amide bond (-CONH-)); if it is a hydrophobic end, it will be coated on the cerium oxide nanoabrasive, resulting in a decrease in its suspension. When a variety of silane coupling agents are mixed, the effect of improving the suspension of the modified cerium oxide nanoabrasive is better.
[0043] Example 4 The specific implementation method is consistent with Example 1, except that only the ratio of the silane coupling agent to the cerium oxide nanoabrasive is changed.
[0044] When the mass ratio of cerium oxide nanoparticles to silane coupling agent = 30:1, 5 g of cerium oxide nanoparticles and 0.167 g of KH550 were used; When the mass ratio of cerium oxide nanoparticles to silane coupling agent = 20:1, 5 g of cerium oxide nanoparticles and 0.25 g of KH550 were used; When the mass ratio of cerium oxide nanoparticles to silane coupling agent = 10:1, 5 g of cerium oxide nanoparticles and 0.5 g of KH550 were used; When the mass ratio of cerium oxide nanoparticles to silane coupling agent = 5:1, 5 g of cerium oxide nanoparticles and 1 g of KH550 were used; The D50 value was determined according to the suspension test in Example 1. The experimental results are shown in Table 3.
[0045] Table 3: Effect of different mass ratios of cerium oxide nanoparticles to silane coupling agent on the suspension properties of modified cerium oxide nanoabrasives.
[0046]
[0047] Example 5 The specific implementation method is the same as that of Example 1, except that different short-chain organic acids are used, namely, glutamic acid, aspartic acid, cysteine, serine, threonine, histidine and glycine are used for the reaction.
[0048] The D50 value was determined according to the suspension test in Example 1, and the experimental results are shown in Table 4. The infrared spectra of the samples modified with glutamic acid, aspartic acid and KH550 are shown in Figure 3 , located at 2360 cm -1 The characteristic peak at 1400 cm -1 A new peak appears at , indicating that glutamic acid and aspartic acid are successfully bridged on the surface of KH550@CeO2.
[0049] Table 4: Effect of different organic carboxylic acids on the suspension properties of cerium oxide nanoabrasives.
[0050]
[0051] It can be seen from the experimental data of Example 5 that the different types of carboxylic acid modifications have a large impact on the suspension stability of the cerium oxide nanoabrasive suspension. The number of carboxyl functional groups in the organic carboxylic acid affects the coupling reaction with the silane coupling agent on the surface of the cerium oxide nano-intermediate. When the number of functional groups is large or the carbon chain of the organic acid is long, it is difficult to couple with the cerium oxide intermediate. The experimental data show that glutamic acid with two carboxyl functional groups can greatly improve the suspension stability of its suspension.
[0052] Example 6 The specific implementation method is consistent with Example 1, except that only the mass ratio of cerium oxide to organic acid is changed.
[0053] When the mass ratio of cerium oxide to glutamic acid = 30:1, 5 g of cerium oxide nanoparticles and 0.167 g of glutamic acid were used; When the mass ratio of cerium oxide to glutamic acid = 20:1, 5 g of cerium oxide nanoparticles and 0.25 g of glutamic acid were used; When the mass ratio of cerium oxide to glutamic acid = 10:1, 5 g of cerium oxide nanoparticles and 0.5 g of glutamic acid were used; When the mass ratio of cerium oxide to glutamic acid = 5:1, 5 g of cerium oxide nanoparticles and 1 g of glutamic acid were used; The D50 value was determined according to the suspension test in Example 1. The experimental results are shown in Table 5.
[0054] Table 5: Effect of different mass ratios of cerium oxide to organic acid on the suspension properties of cerium oxide nanoabrasive.
[0055]
[0056] Example 7 Specific implementation method The method is the same as Example 1, except that only the oil bath temperature and time for synthesizing the cerium oxide intermediate are changed.
[0057] Change the oil bath temperature to 15, 40, 80, 110 o C.
[0058] The oil bath time was changed to 2, 8, and 12 h.
[0059] The D50 value was determined according to the suspension test in Example 1. The experimental results are shown in Table 6.
[0060] Table 6: Effect of different oil bath temperatures and times on the suspension of cerium oxide nanoabrasives.
[0061]
[0062] It can be seen from the experimental data of Example 7 that appropriately increasing the oil bath temperature and extending the oil bath time can improve the suspension stability of the cerium oxide nanoabrasive suspension. The reason is that the oil bath temperature affects the bridging of the silane coupling agent of cerium oxide. If the temperature is too high, it exceeds the boiling point of toluene, thereby affecting the reaction system, while if the temperature is too low, the silane coupling agent will not be bridged to the surface of the cerium oxide abrasive.
[0063] Example 8 Specific implementation method The method is the same as Example 1, except that only the oil bath temperature and time of the synthetic cerium oxide abrasive are changed.
[0064] Change the oil bath temperature to 15, 40, 80, 120 o C.
[0065] The oil bath time was changed to 2, 8, and 12 h.
[0066] The D50 value was determined according to the suspension test in Example 1. The experimental results are shown in Table 7.
[0067] Table 7: Effect of different oil bath temperatures and times on the suspension properties of cerium oxide nanoabrasives.
[0068]
[0069] It can be seen from the above experimental data that the reaction time and oil bath temperature for preparing modified cerium oxide nanoabrasives will affect the suspension stability. Exceeding the appropriate reaction temperature and reaction time will lead to a decrease in its suspension stability.
[0070] Comparative Example 1 The specific implementation method is consistent with Example 1, and the mass ratio of cerium oxide nanoparticles to the silane coupling agent is changed. When the mass ratio of cerium oxide nanoparticles to the silane coupling agent is 40:1, 5 g cerium oxide nanoparticles and 0.125 g KH550 are used; When the mass ratio of cerium oxide nanoparticles to silane coupling agent = 4:1, 5 g of cerium oxide nanoparticles and 1.25 g of KH550 were used; The D50 value was determined according to the suspension test in Example 1. The experimental results are shown in Table 8.
[0071] Table 8: Effect of different mass ratios of cerium oxide nanoparticles and silane coupling agent on the suspension properties of modified cerium oxide nanoabrasives
[0072] Comparative Example 2 The specific implementation method is consistent with Example 1, except that the short-chain organic acid is not used for modification.
[0073] Comparative Example 3 The specific implementation method is consistent with Example 1, except that the silane coupling agent is not used. The experimental results are shown in Table 9.
[0074] Table 9: Effect of not using silane coupling agent on the suspension properties of modified cerium oxide nanoabrasive
[0075] Comparative Example 4 The specific implementation method is consistent with Example 1, and the mass ratio of cerium oxide nanoparticles to short-chain organic acid is changed. When the mass ratio of cerium oxide to glutamic acid is 40:1, 5 g of cerium oxide nanoparticles and 0.125 g of glutamic acid are used; When the mass ratio of cerium oxide to glutamic acid is 4:1, 5 g of cerium oxide nanoparticles and 1.25 g of glutamic acid are used; the D50 value is determined according to the suspension determination experiment in Example 1, and the experimental results are shown in Table 10.
[0076] Table 10: Effect of different mass ratios of cerium oxide to organic acid on the suspension properties of cerium oxide nanoabrasive.
[0077]
[0078] Based on the above data, we can draw the following conclusions: Comparing Example 4 with Comparative Example 1, it can be seen that appropriately increasing the amount of silane coupling agent used within a certain range is beneficial to the suspension stability of the cerium oxide nanoabrasive suspension. The reason is that the increase in the number of silane coupling agents increases the probability of collision with the cerium oxide nanoabrasive, resulting in more contact sites on the surface of the cerium oxide nanoabrasive combining with carboxylic acid, and ultimately increasing the suspension stability of the cerium oxide nanoabrasive suspension. When the content of the silane coupling agent is too low, the silane coupling agent is difficult to effectively collide with the cerium oxide nanoabrasive, ultimately resulting in poor suspension stability.
[0079] Comparing Example 6 with Comparative Example 4, appropriately increasing the amount of short-chain organic acid used within a certain range is beneficial to the suspension stability of the cerium oxide nanoabrasive suspension, but the content of the short-chain organic acid should not be too high. When the content is excessive, it is easy to react by itself and thus affect the modified cerium oxide nanoabrasive; when the content is low, it is difficult to achieve the co-modification effect.
[0080] During use, its solid content needs to be limited. When the solid content is lower than 1% or greater than 20%, it is not conducive to the preservation of the modified cerium oxide nanoabrasive and will reduce its use value. Therefore, in the actual configuration process, the solid content is maintained at 1%-20%.
[0081] It can be seen that when the preparation method of the present invention is used for preparation, the modified nano suspension time can be effectively increased, and the cerium oxide nanoabrasive is modified without adding any additives, thereby greatly improving its suspension stability.
[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a modified cerium oxide nanoabrasive, characterized in that: The steps include: Pre-treating cerium carbonate to obtain cerium oxide nanoparticles; The cerium oxide nanoparticles are mixed with a toluene solution containing a silane coupling agent, heated and stirred in an oil bath for reaction, centrifuged, washed with ethanol, and dried to obtain a cerium oxide intermediate; The short-chain organic acid is prepared into an aqueous solution, the cerium oxide intermediate is mixed with the short-chain organic acid aqueous solution, heated in an oil bath and stirred for reaction, centrifuged, washed with ethanol, and dried to obtain; The mass ratio of the cerium oxide nanoparticles to the silane coupling agent = (30:1) - (5:1); The mass ratio of the cerium oxide intermediate to the short-chain organic acid is (30:1)-(5:1).
2. The method for preparing the modified cerium oxide nanoabrasive according to claim 1, characterized in that: The mass ratio of the cerium oxide nanoparticles to the silane coupling agent is 10:1; Preferably, the mass ratio of the cerium oxide to the short-chain organic acid is 10:
1.
3. The method for preparing the modified cerium oxide nanoabrasive according to claim 1, characterized in that: The silane coupling agent is a mixture of any one or more of γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-(2,3-epoxypropyloxy)propyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-(methacryloyloxy)propyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, γ-aminoethylaminopropyl trimethoxysilane, N-β-(aminoethyl)-γ-aminopropyl methyldimethoxysilane or γ-methacryloyloxypropyl methyldimethoxysilane.
4. The method for preparing the modified cerium oxide nanoabrasive according to claim 3, characterized in that: The silane coupling agent is a mixture of γ-aminopropyl triethoxysilane and / or γ-mercaptopropyl trimethoxysilane, and any one of γ-(2,3-epoxypropyloxy)propyl trimethoxysilane, γ-aminopropyl trimethoxysilane or 3-mercaptopropyl triethoxysilane is added.
5. The method for preparing the modified cerium oxide nanoabrasive according to claim 1, characterized in that: The short-chain organic acid is a mixture of any one or more of glutamic acid, aspartic acid, cysteine, serine, threonine, histidine, glycine, tryptophan, phenylalanine, leucine, methionine, cystine, tyrosine, arginine, isoleucine, proline, asparagine, citric acid, and ethylenediaminetetraacetic acid; Preferably, the short-chain organic acid is glutamic acid.
6. The method for preparing the modified cerium oxide nanoabrasive according to claim 1, characterized in that: In the step of mixing the cerium oxide nanoparticles with a toluene solution containing a silane coupling agent, heating and stirring in an oil bath for reaction, the temperature of the oil bath is 40° C.-110° C., and the time of the oil bath is 2 h-12 h; Preferably, the temperature of the oil bath is 80°C and the time of the oil bath is 5 hours.
7. The method for preparing the modified cerium oxide nanoabrasive according to claim 1, characterized in that: In the step of mixing the cerium oxide intermediate with the short-chain organic acid and heating and stirring in an oil bath for reaction, the temperature of the oil bath is 40° C.-120° C., and the time of the oil bath is 2 h-12 h; Preferably, the temperature of the oil bath is 80°C and the time of the oil bath is 5 hours.
8. The method for preparing the modified cerium oxide nanoabrasive according to claim 1, characterized in that: The pre-treatment step includes calcination, the calcination temperature is 400°C-1200°C, and the calcination time is 6h-48h; Preferably, the calcination temperature is 800°C and the calcination time is 30h.
9. A method for using the modified cerium oxide nanoabrasive prepared by the method for preparing the modified cerium oxide nanoabrasive according to any one of claims 1 to 8, characterized in that: The steps include: The modified cerium oxide nano-abrasive is mixed with water to form a suspension, and the solid content is maintained at 1%-20%.
Citation Information
Patent Citations
Modified nanometer cerium oxide and preparation and application thereof
CN101659850A
Preparation and desulfurization application of cerium dioxide with ultra-small particle size
CN115448353A
Ethylenediamine tetraacetic acid grafted cerium oxide composite abrasive particle as well as preparation method and application thereof
CN116285895A
Method for preparing cerium-based polishing agent
KR1020060005794A
Process for chemically mechanically polishing substrates containing silicon oxide dielectric films and polysilicon and / or silicon nitride films
US20130171824A1
Cited By
Deep eutectic solvent modified cerium oxide reinforced chloroprene rubber composite material and preparation method thereof
CN122188255A